Exonic variants undergoing allele-specific selection in cancers - Qiyuan Li; Yuanyuan Zeng; Janet Wang; Hongkun Fang; Jintao Guo; Liying Yu; Taoling Zhong; Chaoqun Xu; Matthew Freedman; Thomas LaFramboise (BMC, 2021)
Abstract Background Allelic imbalance (AI) in tumors is caused by chromosomal and sub-chromosomal gains and losses. Results We evaluated AI at 109,086 germline exonic SNP loci in four cancer types, and identified a set of SNPs that demonstrate strong tumor allele specificity in AI events. Further analyses demonstrated that these alleles show consistently different frequencies in the cancer population compared to the healthy population and are significantly enriched for predicted protein-damaging variants. Moreover, genes harboring SNPs that demonstrate allele specificity are enriched for cancer-related biological processes and are more likely to be essential in cancer cells. Conclusions In summary, our study provides a unique and complementary method to identify genes and variants that are relevant to carcinogenesis.